Eight Levels of writing problems: Critical Examination of Research Findings Putting Them into Practice - Nepal, Arun (Journal of NELTA, 2024)
This article critically examines the findings of the large-scale action research that identified eight levels of writing problems faced by Bachelor’s first-year students. The same writing problems are examined, putting them into practice after a year of the completion of the action research. The aim was to measure their credibility and trustworthiness in a natural classroom setting, which was identical to the action research. The research context for both studies was also similar except for the participants. The participants were also selected purposefully, and the data were collected through tests in both studies. The tests were administered among the twelve students in the action research and the thirteen students in this study. The findings indicated that the participants in both studies faced the eight levels of writing problems, and three writing problems, namely sentence level (SL), paragraph level (PL)and full body level (FBL) were found more difficult for almost all of them. Thus, this article further justified the need to involve students in writing processes as a part of their academic life to help them develop writing skills and achieve academic success.